Representações sociais dos professores sobre a inclusão escolar de deficientes na EJA - CONDE, Joyce Maria da Silva (2021)
The present study analyses the social representations of the teachers about school inclusivity for students with disabilities inside EJA (Youth and Adult Education). The theoretical-methodological referential is based in the Social Representations Theory, in Jodelet’s (2001) processual field. As such, to attend to the proposed objectives, this study was developed in two steps: documentary survey (statistical data) and interviews with five teachers from Bragança’s Municipal School System (in the Brazilian state of Pará). Thereby, for the field of analysis’ organization, the Three Constituent Dimensions Theory (subjects, contexts and meanings) was considered. The results reveal: EJA’s teacher subjects that construct their identity, including beginning from the teaching time in the EJA. In the context of the circulation of the representations the indicatives point the significant decrease to the number of enrollment to EJA (Brazil/ Pará/ Region of the Caetés/ Bragança). This data confirms not only the exclusionary process experienced in the Youth and Education programs, but also the public service’s neglect in this teaching modality, in addition to the denial of rights in relation to the subjects from EJA. The meanings that present the teachers’ discourses about inclusion for students with disabilities inside of EJA enabled the construction of the imagetic figure that made it possible to identify the meanings constructed by the teachers about inclusion inside EJA, of the images that are constructed about the docent methods for the inclusion of people with disabilities inside EJA and lastly, the practices constructed as from the meanings of inclusion and the constructed images about the docent methods in EJA classes that have students with disabilities.